Intramolecular transesterification of depsides yields fluorescent 1H-isochromen-1-ones: Application as a chemical probe for lichen determination. (June 2022) - Ferron, S.; Jéhan, P.; Guillory, X.; Uriac, P.
Abstract: The reactivity of eight purified depsides obtained from six european lichens and that display as 2-oxoalkyl chain in ortho -position of the ester bond was explored. These depsides were found to lead to 1 H -Isochromen-1-ones, which exhibit a distinctive blue fluorescence at 365 nm, in the presence of a 10% aqueous solution of KOH. A mechanistic explanation, involving the formation of an enolate intermediate and intramolecular transesterification, was proposed and validated by DFT. By exploiting this fluorescent phenomenon, we conceived a chemical probe (the KUV probe ) that is useful for lichen determination, as exemplified on a selection of European Porpidia species . Graphical abstract: Image 1 Highlights: Extraction from lichens and purification of eight depsides bearing a δ-keto ester moiety. Intramolecular transesterification under basic conditions yield blue fluorescent 1 H -isochromen-1-ones. Mechanistic proposition and DFT validation of this rearrangement involving an enolate intermediate. Conception of a new chemical probe named KUV probe for lichen determination: application to European Porpidia lichens.